2016
DOI: 10.5505/agri.2016.00378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subclinical Atherosclerosis in Migraine Patients by Ultrasound Radiofrequency-Data Technology, Preliminary Results

Abstract: SummaryObjectives: Migraine is a headache disorder affecting approximately 12% of the population, predominantly female individuals. Migraine has been associated with vascular events such as stroke and cardiovascular disease. The close connection between these vascular disorders and atherosclerosis is well known. Carotid artery intima-media thickness (CAIMT) is a marker for detection of subclinical atherosclerosis. The present study is an analysis of the presence of subclinical atherosclerosis in migraine patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Seven studies were finally included in the meta-analysis (Table 1). 1719,2528 All seven papers were published between 2010 and 2016 and were carried out in five countries: Egypt, Turkey, Germany, Croatia, and Italy. All studies enrolled patients with both MA and MO, except for the trial by Liman et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies were finally included in the meta-analysis (Table 1). 1719,2528 All seven papers were published between 2010 and 2016 and were carried out in five countries: Egypt, Turkey, Germany, Croatia, and Italy. All studies enrolled patients with both MA and MO, except for the trial by Liman et al.…”
Section: Resultsmentioning
confidence: 99%
“…Carotid artery stenosis is an important change in patients with ischemic stroke, 13,14 and carotid intima-media thickness (IMT) is often assessed to monitor the pathological condition of atherosclerosis in clinical practice. 15 Some studies have also assessed this index in patients with migraine 16,17 and showed that migraine patients had greater carotid IMT than controls. 1720 IMT may thus be a possible marker for assessing the risk of migraine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Tatar et al, carotid intima-media thickness was evaluated between 25 women with migraine and 27 healthy women with a mean age of 33 ± 9 years and In the migraine group, a statistically significant increase was found and the association of migraine patients with subclinical atherosclerosis was reported [10]. In a similar study by Hamed et al, between 44 migraine patients in remission, 19 tension-type headache patients and 35 control groups, the thickness of carotid intima-media were compared and CIMT measurements of migraine with and without aura were significantly higher than tension headache and control groups [20].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in paediatric migraine patients, carotid intima-media thickness measurements were shown to be higher in patients with migraine than in the control group [9]. In another study conducted with 25 adult female migraine patients, carotid intima-media thickness was higher compared to the control group and it was concluded that migraine patients were prone to subclinical atherosclerosis [10].…”
Section: Introductionmentioning
confidence: 97%